Analisis Kesehatan Likuiditas pada Lembaga Perkreditan Desa (LPD) Desa Adat Blahkiuh Kecamatan Abiansemal Kabupaten Badung (Jurnal Agribisnis dan Agrowisata, 2026)
Liquidity Health Analysis of Village Credit Institutions (LPD) in Blahkiuh Custom Village, Abiansemal District, Badung Regency. LPD constitutes one type of microfinance organization present in Bali. Their purpose is to promote rural community economic growth through savings and capital participation, creating equal opportunities and business prospects among villagers. Demonstrating sound liquidity health of LPD helps build public trust towards them, enabling better understanding of how well they fulfill all immediate obligations. This liquidity assessment benefits various stakeholders such as landowners, managers, depositors (borrowers and savers), trainers, and supervisors of LPD. By analyzing liquidity health based on liquidity ratios like current ratio, quick ratio, cash ratio, and inventory turnover rate, this study aims to understand the liquidity health of LPD Desa Adat Blahkiuh during the years 2019–2023. Quantitative and qualitative methods were employed along with calculations of liquidity ratios. The findings reveal that the liquidity health of LPD Desa Adat Blahkiuh was categorized as follows according to the measured liquidity ratios: Current Ratio: Sufficiently healthy, Quick Ratio: Sufficiently healthy, Cash Ratio: Sufficiently healthy, Inventory to Net working Capital: Unhealthy.
Keywords: LPD; liquidity health; liquidity ratios